Strategies Against Political Dynasty in Banjar Mayor Election 2018 - Wiwi Widiastuti; Taufik Nurohman (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
The issue of the political dynasty in Banjar City has emerged since the last ten years after two periods of the leadership of Herman Sutrisno were continued by Ade Uu Sukaesih who is his wife. Entering the second period Ade Uu Sukaesih re-nominated as Mayor of Banjar, again the issue of political dynasty reappeared. The issue of the dynasty was then used as an opportunity for political opponents in participating in political contestation. Through this research, the author wants to find out how the political marketing strategies of Maman Suryaman and Irma Bastaman's pair against the political dynasty. This study uses political marketing theory and descriptive qualitative research methods with sampling techniques namely purposive sampling. The results of the study prove that the dynastic issue that accompanied Ade Uu Sukaesih's journey began to fade with the vote in the second period of Ade Uu Sukaesih's leadership which declined from the first period to the second period. Although the pair Maman Suryaman and Irma Bastaman failed to defeat the incumbent, they began to shift the political map in Banjar City and became one of the bearers of the change movement for Banjar with superior marketing strategies through social media and combing deeper into urban society. The weakness of Maman Suryaman and Irma Bastaman's partners lies in their focus on social media by putting aside the functions and roles of print and electronic media. In addition, they also focus too much on the millennia generation and put aside other segments such as rural communities, laborers as well as farmers who are not all technology literate so that political campaigns through social media are not always effective.